THE ROLE OF GAMIFICATION TO INTENTION THROUGH ATTITUDE ON MARKETPLACE APP ADOPTION - Lady, Lady; Defen, Defen; Nurjanah, Listia (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This research aims to examine the social influence and shopping motivation in shaping attitudes towards marketplace applications within the context of gamification, as well as to explore how gamification in e-commerce has been shown to increase visitor numbers. The approach used by researchers is a quantitative approach with associative method, with data collection through distributing questionnaires to 337 respondents who has played marketplace app games in Indonesia. The data were analyzed using SmartPLS. The test results show that social influence, recognition, reciprocal benefits have a significant influence on attitudes. However, hedonism does not have a significant influence on attitudes. Meanwhile, attitude also shows a strong mediating influence in linking social influence, recognition, reciprocal benefits to continuous use intentions, but cannot mediate hedonic with continued use intentions and intention to spread WOM. This research explores the relationship between the variables such as social influence, recognition, reciprocal benefit, and hedonic value, which are mediated by attitude to continued use intention and intention to spread WOM in marketplace app, which have hardly been discussed in previous research.